The Virtues of Theory: How Some Academics Succeeded – Big Time – in Reaching Non-Academic Audiences. Issue 2 (3rd April 2019) - Feldman, Gregory
ABSTRACT: This is a short essay stimulated by Why Anthropologists Don't Reach the Public: A Rumination on Books of Thomas Hylland Eriksen, by Gordon Mathews (DOI:https://doi.org/10.1080/00664677.2018.1502074 ).